Vaccination of on-farm cattle against heartwater : safety and efficacy of Ehrlichia ruminantium (Welgevonden) vaccine - Mans, Ben J. (Barend Johannes) (University of Pretoria, 2025)
Dissertation (MSc (Veterinary Sciences))--University of Pretoria, 2018.